God, gender, and family trauma : how rereading Genesis can be a revelation - Driver, Cory Thomas Pechan (Fortress Press, 2025)
"Driver uses trauma-informed scholarship and Jewish midrash to invite readers into new understandings of Genesis. Viewing figures such as Sarah, Joseph, Tamar, and Dinah through this lens sheds valuable light on what the Bible can teach us about gender and family trauma. These ancient stories have implications for our own lives in ministry"--